Grading characterization and yield stress prediction based on paste stability coefficient - CHENG Hai-yong; WU Shun-chuan; WU Ai-xiang; CHENG Wei-hua (工程科学学报)
Paste backfilling has become an important support technology in green mining construction. The flowability and rheology performance of paste determine whether the slurry can be transported normally. As such, the evaluation of flowability and rheology of paste are important factors in the reliability of paste transportation. Because paste has the three characteristics of fluidity, stability and plasticity, traditional two-phase flow theory cannot effectively analyze its plug flow. However, it is an effective method for analyzing and evaluating the fluidity of the paste based on rheology theory, and the yield stress is an important parameter for evaluating the rheological characteristics of paste. Due to the different properties of the materials in different mines, it is difficult to analyze the factors that influence yield stress. Several experiments have been conducted on a variety of tailings from different mines, including a gradation characterization and influence experiment, a rheology experiment on materials of similar densities, and double-factor rheological experiments based on the concentration and sand ratio. Combined with mesoscopic structure analysis technology, the evolution mechanism of yield stress was studied. The results indicate that the stability coefficient of paste can effectively reflect the gradation, and can also reflect the comprehensive characteristics of the granule and fluid. The yield stress increases significantly with the paste stability coefficient and increases exponentially with the concentration. At the same time, yield stress is characterized by negative exponential growth with density. The error range of this yield stress prediction model for unclassified tailings paste is within 10%. The mesoscopic structure analysis shows that yield stress is mainly controlled by gradation and flocculent structure. The gradation constitutes the foundation for the plasticity and stability of the slurry. The flocculent structure transforms free water into the semi-stable form of adsorptive water, which causes the macro-evolution of the yield stress.